On the (un‐)adoption of JavaScript front‐end frameworks. (18th October 2021) - Ferreira, Fabio; Borges, Hudson Silva; Valente, Marco Tulio
Abstract: JavaScript is characterized by a rich ecosystem of libraries and frameworks. A key element in this ecosystem are frameworks used for implementing the front‐end of web‐based applications, such as Vue and React . However, despite their relevance, we have few works investigating the factors that drive the adoption—and un‐adoption—of front‐end‐based JavaScript frameworks. Therefore, in this article, we first report the results of a survey with 49 developers where we asked them to describe the factors they consider when selecting a front‐end framework. In the second part of the work, we focus on projects that migrate from one framework to another since JavaScript's ecosystem is also very dynamic. Finally, we provide a quantitative characterization of the migration effort and reveal the main barriers faced by the developers during this effort. Although not completely generalizable, our central findings are as follows: (a) popularity and learnability are the key factors that motivate the choice of front‐end frameworks in JavaScript; (b) from the 49 surveyed developers, one out of four have plans to migrate to another framework in the future; (c) the time spent performing the migration is greater than or equal to the time spent using the old framework in all studied projects. We conclude with a list of implications for practitioners, framework developers, tool builders, and researchers.